PERTUMBUHAN DAN PRODUKSI TOMAT CHERRY (Lycopersicon esculentum Miller.) PADA KONSENTRASI NUTRISI YANG BERBEDA DENGAN SISTEM HIDROPONIK - Grecya Manalu (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2021)
Increased growth and production of cherry tomato, especially in the lowlands is influenced by the availability of water, humidity, and cultivation technology of plants, so it takes hydroponic system to realize the growth and production enhancement of cherry tomato. This research aims to identify the proper concentration of nutrient on the growth and production of cherry tomato with hydroponic system. This research was conducted at Screenhouse of Royal Sumatera Housing, Medan Tuntungan (± 32 meters above sea level), from March to August 2017. The research used Completely Randomized Design with one treatment factor that is nutrition concentration (1300 ppm,1750 ppm, and 2200 ppm). The results showed that the nutrient concentration of 1750 ppm increase the growth of stem diameter. Nutrient concentration of 2200 ppm increases plant height, the speed of flowering, number of branches, number of segments, fruit weight, and number of fruits.